Kinetic Study of the Adsorption of Polyphenols from Olive Mill Wastewater onto Natural Clay: Ghassoul - Safae Allaoui; Mohammed Naciri Bennani; Hamid Ziyat; Omar Qabaqous; Najib Tijani; Najim Ittobane (Journal of Chemistry)
The aim of this study is based on natural clay as an adsorbent in the elimination of polyphenols from olive mill wastewater (OMW). This clay was analyzed using XRD, SEM/EDX, FTIR, surface area measurement (BET method), thermal analysis (TGA/DTA), and X-ray fluorescence (XRF) and then used in adsorption experiments. The results reveal that the best quantity of adsorption of polyphenols is 161 mg/g at the temperature of 25°C, but they decrease at 35°C and 45°C. A great agreement with pseudo-second-order and Freundlich model is represented by kinetic and isotherms models, and several parameters such as ΔG0, ΔS0, and ΔH0 were determined using the thermodynamic function relationship.